Elaboración e implementación del plan de mantenimiento predictivo y preventivo para la empresa Probalsa s.a. del cantón el Carmen, año 2014 - Díaz Patrón, Janner Antonio (2015)
This research work will result present the company Probalsa. The development and implementation of a plan of predictive and preventive maintenance Producers Probalsa C.Ltda raft is a logging company with forty years in the canton El Carmen Manabí It is the most important of this canton and one of the most representative of the province making it a potential candidate At present the company Probalsa S.A. It is implementing the PLAN predictive and preventive maintenance , where its production facilities play an important role , the equipment and machinery will always be used in the processing of balsa wood where the ability of human talent is one of the cornerstones and the company does not have an implementation of a plan of predictive and preventive maintenance , presented unforeseen and frequent damage frequently delaying the production process causing economic losses and long hours in each process. Considering the technical parameters diagnosis it was performed to determine the condition of the machinery and equipment of the company Probalsa the review of surveys and analysis of the interview to the Manager of the company Probalsa technical and data thrown together with the inventories carried out at the equipment and machinery was obtained better maintenance Development and implementation established and according to the Plan Predictive and Preventive Maintenance in the company PROBALSA implementation ensures the life of the equipment and machinery reaching the objectives.